2012
DOI: 10.1111/j.1757-7861.2012.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Cement Embolism Associated with Percutaneous Vertebroplasty or Kyphoplasty: A Systematic Review

Abstract: Therapeutic vertebral cement augmentation for the treatment of painful skeletal diseases, although widely applied for more than several decades, still has not thoroughly resolve the problem of cement extravasation. Based on a review of literature published, the present study was to provide a systematic review of the current understanding of pulmonary cement embolism (PCE) associated with percutaneous vertebroplasty (PVP) or percutaneous kyphoplasty (PKP), and to summarize the incidence, clinical features, prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
67
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(71 citation statements)
references
References 74 publications
1
67
0
3
Order By: Relevance
“…Common local adverse effects include pain, bleeding and infections 7. Venous leaks from vertebroplasty are very common4 5 with Lim et al 7 quoting 24% venous leaks from total 73% leaks reported. Serious systemic complications include paraplegia, paradoxical cerebral embolism and renal artery infarction 7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Common local adverse effects include pain, bleeding and infections 7. Venous leaks from vertebroplasty are very common4 5 with Lim et al 7 quoting 24% venous leaks from total 73% leaks reported. Serious systemic complications include paraplegia, paradoxical cerebral embolism and renal artery infarction 7.…”
Section: Discussionmentioning
confidence: 99%
“…Serious systemic complications include paraplegia, paradoxical cerebral embolism and renal artery infarction 7. However, there have been only 51 reported cases of pulmonary embolism caused due to cement migration through IVC5 with varying incidence of 0.9–23% 1 6. Cement leaks into the IVC showed a statistically significant (p=0.03) correlation with cement pulmonary embolism 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This complication occurs relatively often in vertebroplasties and kyphoplasties of the thoracic and lumbar spine, with rates ranging from 2.1% to 26%. 2,8,16,24,49,52 Embolization via the arterial circulation of the vertebral artery into the posterior brain circulation has been described in 1 case and led to cerebellar symptoms and lateral homonymous hemianopia after the vertebroplasty. Imaging in this case revealed an acute cerebellar and occipital infarction due to a cement embolism of the vertebral artery.…”
Section: Discussionmentioning
confidence: 99%
“…1 Incidence estimates vary widely from 2% to 26%. 2 The management of asymptomatic pulmonary cement embolism remains uncertain; our decision was informed by an analysis of a case report by Krueger and colleagues that suggested anticoagulation treatment only for centrally distributed emboli.…”
mentioning
confidence: 99%